Crowds, Clouds, Politics and Aesthetics, Flipping Again - Leslie, Esther (The Nordic Journal of Aesthetics, 2014)
This paper seeks an urban poetics under the pressures of flux, polyglot babble and the rise of technoculture. In so doing it traces the intertwinements of aesthetics and politics as they manifest over the last 150 years. Charles Baudelaire’s poetry is characterised as a delirious response to the delirium of capitalist modernity, in which ‘words rise up’, as he puts it, but it is a also a barometer, which measures the degrees of entwinement of aesthetics and revolutionary politics in the subsequent years, for one in Walter Benjamin’s interpretation in the 1930s and in the wild translations of the poet by Sean Bonney in 2008 in the collection ‘Baudelaire in English’.